The emerging risk of exposure to nano(micro)plastics on endocrine disturbance and reproductive toxicity: From a hypothetical scenario to a global public health challenge. (June 2020) - Amereh, Fatemeh; Babaei, Mohammad; Eslami, Akbar; Fazelipour, Simin; Rafiee, Mohammad
Abstract: Humans are potentially exposed to nano(micro)plastics, however their interaction with tissues and cells in humans remains largely unknown. This premise is particularly notable with nano-sized plastic particulates, a potentially most pernicious form of plastic pollution. In this study, even in a hypothetical scenario in terms of dose (1, 3, 6 and 10 mg/kg-day) and exposure time (five weeks), the potential endocrine disturbances with particular reference to reproductive toxicity of polystyrene nanoplastics (PS NPs, average size = 38.92 nm) was studied in male rats considering biomarkers of semen quality, changes in hormonal milieu and molecular signatures of endocrine disruption. Sperm DNA integrity and its chromatin structure were also analyzed. There observed significant inverse associations between exposure to PS NPs and serum concentrations of testosterone, luteinizing hormone (LH) and follicle-stimulating hormone (FSH). Tissue and cell impairments were also noticed even at the lowest tested dosage, though the severity of lesions followed a clear dose-response pattern. DNA damage as well as alterations in sperm morphology and viability were evident, again proportionally with the amount of exposure dosage. RT-qPCR data were in accordance with the results of physio-histological alterations and fluorescence imaging, as significant down-regulation of PLZF, DAZL, FSH and LH gene expressions were noticed in the testis of exposed animals, suggesting that exposure interferes with spermatogenesis and also with HPT-axis. However, among those with highest exposure dosage, expressions of FSH and LH were significantly increased. ABP modulation further revealed evidence of a nonlinear dose response. The association between PS NPs exposure and GnRH was indeed in an unexpected positive direction, though these end-points were less sensitive at higher doses. Although additional evidence is warranted, the present work provides new insights into the possible risks of plastic nanoparticles exposure in humans, especially since the problem is growing and will persist for a long time. Graphical abstract: Image 1 Highlights: Rats were orally exposed to virgin and fluorescently labeled polystyrene nanoplastics. Early warning signs of reproductive toxicity in rats from the ingestion of PS. A significant down-regulation of PLZF, DAZL, FSH and LH gene expressions were found. Endocrine disturbance was ascribed to NPs bioaccumulation and histological lesion.